Effect of Dietary Supplementation with Different Levels of Palm Pollen on the Physiological Performance of the Broiler - Ezzat , Hasanain N. (International Journal of Poultry Science, 2018)
Objective: This experiment was conducted to study the effects of Palm pollen on the levels of lipids, proteins, enzymes, glucose, phosphorus, calcium and uric acid concentrations in the blood of broilers. Materials and Methods: Ninety-six chicks of the Ross 308 breed of both sexes, with an initial weight of 38 g/chick, were used. Chicks were distributed randomly into 4 treatment groups with 3 replicates (8 birds/replicate). Experimental treatments were divided as follows: T1-Control, T2-diet supplemented with palm pollen 200 g/100 kg, T3-diet supplemented with palm pollen 400 g/100 kgt and T4-diet supplemented with palm pollen 600 g/100 kg. A completely randomized design (CRD) was used to investigate the effects of the studied treatments on different traits. Results: The plasma lipid panel indicated that there were no significant differences among treatments for all characteristics in the 3rd and 5th weeks of the experiment, except for cholesterol and low-density lipoprotein (LDL) in the 3rd week, where the supplemented treatment resulted in a significant decrease for these characteristics. The results of the blood enzyme test indicated that T1 resulted in significantly increased (p<0.05) levels compared to the other treatments in the 3rd week of the experiment. The results also show that there were no significant differences among treatments in the 5th week of the experiment when measuring aspartate amino transferase (AST) and alkaline phosphatase (ALP), but it was found that there were significant differences when measuring alanine amino transferase (ALT), where T3 was higher than the rest of the treatments in the 3rd week of the study. It is worthwhile to mention that there was a significant difference (p<0.05) for the supplementing treatments in the 5th week when measuring blood glucose. The uric acid concentration showed significantly higher results (p<0.05) for T1 than the rest of the treatments. It was also found that calcium was significantly higher for T4 in the 3rd week of the study, while phosphorus was significantly higher for all supplementing treatments in the 3rd week of the study. Conclusion: The addition of palm pollen to the diet improved all the qualities studied.